2011
DOI: 10.1093/ndt/gfr503
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 combined with tacrolimus in de novo renal transplantation: 1-year, multicenter, open-label randomized study

Abstract: FTY720 combined with tacrolimus and steroids did not show a significant therapeutic advantage over MMF for the prevention of acute rejection in de novo renal transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…Originally, fingolimod was evaluated as a treatment for renal transplant rejection, wherein patients received higher doses of fingolimod (2.5 and 5 mg), in combination with cyclosporine, tacrolimus, and/or steroids [3,4,5,6]. In this context, macular edema (ME) has been identified as a specific adverse event of fingolimod in renal transplant patients [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, fingolimod was evaluated as a treatment for renal transplant rejection, wherein patients received higher doses of fingolimod (2.5 and 5 mg), in combination with cyclosporine, tacrolimus, and/or steroids [3,4,5,6]. In this context, macular edema (ME) has been identified as a specific adverse event of fingolimod in renal transplant patients [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, macular edema (ME) has been identified as a specific adverse event of fingolimod in renal transplant patients [3,4,5,6]. In the phase II core study of fingolimod in multiple sclerosis (MS) and its extensions, two high doses of fingolimod (1.25 and 5.0 mg) were administered and none of the patients developed ME [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…FTY720 {fingolimod; 2-amino-2-[2-(4-octylphenyl)ethyl]-1,3-propanediol hydrochloride} is a sphingosine-1-phosphate (S1P) analog originally developed as a novel immunosuppressant and has currently been tested in phase III studies for the treatment of renal transplantation. 7 The mechanism of immunosuppressive action of FTY720 has not been fully elucidated, although a characteristic depletion of circulating lymphocytes in the peripheral blood and a reduction of lymphocyte infiltration into injured tissues by accelerating lymphocyte homing into peripheral lymph nodes has been observed in some experimental models. 8 More interestingly, previous studies have shown that FTY720 attenuates renal injury in many experimental models, such as antithy1-induced chronic glomerulosclerosis, 9 renal ischemia reperfusion injury, 10 subtotal nephrectomy, 11 experimental hypertensive nephropathy 12 and antiglomerular basement membrane glomerulonephritis.…”
Section: Introductionmentioning
confidence: 99%
“…16 Coexisting disease like diabetes, diabetic retinopathy, retinal vascular disease, past ocular surgery, and uveitis increase the risk of ME. 16,17 In patients who develop fingolimod-associated ME, cessation of the drug results in the resolution of symptoms.…”
Section: 17mentioning
confidence: 99%